Fenomena âEntertainment Architectureâ di Indonesia dan Perkembangan dalam Arsitektur - Nuffida, Nur Endah (EMARA Indonesian Journal of Architecture, 2016)
The entertainment architecture phenomenon that started in many developed countries in the second half of the 20th century has marked the birth of architectural designs with their primary purpose of providing interactive entertainments for their users. This literature study aims for analyzing a similar phenomenon that grows as an archetype of architectural designs, particularly in Indonesia. The method used in this study is a qualitative research method with naturalistic paradigm. The purpose of this study is to investigate and find the meaning of entertainment architecture, certain characteristics in the form of visual and architectural forms and how these characteristics can be read as a type in the development of architecture. The results of the study is to conclude that the phenomenon of entertainment architecture in Indonesia can be read as the development of new ideas in thinking and making architecture through the figure, looks, and its form, that Â is different from the language of pre-existing buildings